2020
DOI: 10.21037/jtd-2019-abc-03
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided percutaneous needle biopsy skill for peripheral lung lesions and complications prevention

Abstract: Background: To investigate puncture skills and complications prevention in ultrasound-guided percutaneous needle biopsy for peripheral lung lesions. Methods: Ninety-two peripheral lung lesions in 92 patients, detected via computed tomography (CT) and also visible on ultrasound, were retrospectively analyzed. All patients underwent percutaneous peripheral lung lesion needle biopsy under traditional ultrasound or contrast enhanced ultrasound (CEUS) guidance paying attention to avoiding necrotic areas and large b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
3
14
1
3
Order By: Relevance
“…There were no mortalities in all procedures. The results were comparable to previous studies that included various lesion size and reported rates of pneumothorax and hemorrhage ranging from 1%~6% and 3.3%~5.1%, respectively (2,6,12). Influence factors regarding patient characteristics, tumor profiles, needle size and needle passage were analysed.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…There were no mortalities in all procedures. The results were comparable to previous studies that included various lesion size and reported rates of pneumothorax and hemorrhage ranging from 1%~6% and 3.3%~5.1%, respectively (2,6,12). Influence factors regarding patient characteristics, tumor profiles, needle size and needle passage were analysed.…”
Section: Discussionsupporting
confidence: 85%
“…In China, US-guided biopsy is usually preferred for PPLs, while CT-guided procedures are mainly recommended for lesions that cannot be displayed by ultrasound (6). Although CT-guided procedures have been well established in a previous study with a similar diagnostic rate compared with US-guided procedures for PPLs, a higher incidence of postprocedural pneumothorax were observed (7).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Computed Tomography (CT) offers the most accurate method of localizing the lung lesions regardless of its distance from skin and provides relevant information on needle trajectory within the lung as well. 1 Commonly described complication of lung biopsy is pulmonary haemorrhage leading to haemoptysis or hemothorax. 2 Risk of various complications is affected by different parameters such as biopsy needle size, lesion size, lesion depth from pleura, number of pleural punctures during biopsy, needle traversing through fissure and emphysema in the path of the biopsy.…”
Section: Introductionmentioning
confidence: 99%